Inhibition of G9a by a small molecule inhibitor, UNC0642, induces apoptosis of human bladder cancer cells - Cao Yue-peng; Sun Jing-ya; Li Mei-qian; Dong Yu; Zhang Yuan-heng; Yan Jun; Huang Rui-min; Yan Xiang (Acta Pharmacologica Sinica, 2019)
Urinary bladder cancer (UBC) is characterized by frequent recurrence and metastasis despite the standard chemotherapy with gemcitabine and cisplatin combination. Histone modiﬁers are often dysregulated in cancer development, thus they can serve as an excellent drug targets for cancer therapy. Here, we investigated whether G9a, one of the histone H3 methyltransferases, was associated with UBC development. We ﬁrst analyzed clinical data from public databases and found that G9a was signiﬁcantly overexpressed in UBC patients. The TCGA Provisional dataset showed that the average expression level of G9a in primary UBC samples (n = 408) was 1.6-fold as much as that in normal bladder samples (n = 19; P < 0.001). Then we used small interfering RNA to knockdown G9a in human UBC T24 and J82 cell lines in vitro, and observed that the cell viability was signiﬁcantly decreased and cell apoptosis induced. Next, we choosed UNC0642, a small molecule inhibitor targeting G9a, with low cytotoxicity, and excellent in vivo pharmacokinetic properties, to test its anticancer effects against UBC cells in vitro and in vivo. Treatment with UNC0642 dose-dependently decreased the viability of T24, J82, and 5637 cells with the IC50 values of 9.85 ± 0.41, 13.15 ± 1.72, and 9.57 ± 0.37 μM, respectively. Furthermore, treatment with UNC0642 (1−20 μM) dose-dependently decreased the levels of histone H3K9me2, the downstream target of G9a, and increased apoptosis in T24 and J82 cells. In nude mice bearing J82 engrafts, administration of UNC0642 (5 mg/kg, every other day, i.p., for 6 times) exerted signiﬁcant suppressive effect on tumor growth without loss of mouse body weight. Moreover, administration of UNC0642 signiﬁcantly reduced Ki67 expression and increased the level of cleaved Caspase 3 and BIM protein in J82 xenografts evidenced by immunohistochemistry and western blot analysis, respectively. Taken together, our data demonstrated that G9a may be a promising therapeutic target for UBC, and an epigenetics-based therapy by UNC0642 is suggested.